Reconstructing the Position of Qur’anic Memorization in Bloom’s Taxonomy: From Lower-Order Thinking Skills (LOTS) to Spiritual Higher-Order Thinking Skills (HOTS) - Eva Latipah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
Bloom’s Taxonomy traditionally positions memorization at the lowest cognitive level (remember) and categorizes it as a lower-order thinking skill (LOTS). This view often reduces memorization to a mechanical process with limited intellectual value compared to critical and creative thinking. In the tradition of Islamic education, however, particularly in Qur’anic memorization, memorization plays a central role that combines cognitive, spiritual, and affective dimensions, shaping students’ character, morality, and scholarly identity. This study seeks to reconstruct the position of Qur’anic memorization within Bloom’s Taxonomy, aiming to demonstrate that memorization can progress beyond LOTS toward higher-order thinking skills (HOTS) while simultaneously nurturing spiritual development. A qualitative descriptive-analytical design was employed, combining a literature review of Bloom’s Taxonomy and Islamic pedagogy with in-depth interviews involving tahfidz teachers, Islamic education lecturers, and Qur’an-memorizing students. The collected data were analyzed thematically to capture both empirical experiences and conceptual interpretations. The findings reveal that Qur’anic memorization provides a foundation for understanding, application, analysis, evaluation, and even the creation of new ideas rooted in Qur’anic values. This research concludes that memorization should not be seen as a low-level skill but as an epistemological and spiritual instrument that integrates knowledge, faith, and ethical practice, enriching educational excellence and inspiring innovative pedagogical approaches.